Toxicologic/transport properties of NCS-382, a γ-hydroxybutyrate (GHB) receptor ligand, in neuronal and epithelial cells: Therapeutic implications for SSADH deficiency, a GABA metabolic disorder. (February 2018) - Vogel, K.R.; Ainslie, G.R.; McConnell, A.; Roullet, J.-B.; Gibson, K.M.
Abstract: We report the in vitro assessment of pharmacotoxicity for the high-affinity GHB receptor ligand, NCS-382, using neuronal stem cells derived from mice with a targeted deletion of the aldehyde dehydrogenase 5a1 gene (succinic semialdehyde dehydrogenase(SSADH)-deficient mice). These animals represent a phenocopy of the human disorder of GABA metabolism, SSADH deficiency, that metabolically features accumulation of both GABA and the GABA-analog γ-hydroxybutyric acid in conjunction with a nonspecific neurological phenotype. We demonstrate for the first time using MDCK cells that NCS-382 is actively transported and capable of inhibiting GHB transport. Following these in vitro assays with in vivo studies in aldh5a1 −/− mice, we found the ratio of brain/liver GHB to be unaffected by chronic NCS-382 administration (300 mg/kg; 7 consecutive days). Employing a variety of cellular parameters (reactive oxygen and superoxide species, ATP production and decay, mitochondrial and lysosomal number, cellular viability and necrosis), we demonstrate that up to 1 mM NCS-382 shows minimal evidence of pharmacotoxicity. As well, studies at the molecular level indicate that the effects of NCS-382 at 0.5 mM are minimally toxic as evaluated using gene expression assay. The cumulative data provides increasing confidence that NCS-382 could eventually be considered in the therapeutic armament for heritable SSADH deficiency. Graphical abstract: Highlights: NCS-382 pharmacotoxicity was evaluated in SSADH-deficient neural stem cells. NCS-382 is actively transported and inhibits GHB transport in epithelial MDCK cells. NCS-382 showed minimal toxicity in parameters of cellular oxidative stress. NCS-382 minimally impacted cell organelle number, viability, and gene expression. NCS-382 holds promise for treating SSADH deficiency, a disorder of GABA metabolism.